2424. Review of Antimicrobial Susceptibility Profile of Different Nocardia Species, a Tertiary Center Experience. (26th November 2018) - Hamdi, Ahmed; Saleh, Omar Abu; Fida, Madiha; Bryson, Alexandra; Wengenack, Nancy L
Abstract: Background: Nocardia spp. are ubiquitous Gram-positive weakly acid-fast environmental microorganisms. Although considered an opportunistic infection, approximately 1/3 of the reported infections are in immunocompetent patients. Treatment is usually challenging, prolonged and involves multiple agents depending on the site of infection, clinical syndrome and the immune status of the patient. Methods: We conducted a retrospective review of clinical samples with positive cultures for Nocardia spp. from 2011 to 2017. Specimens were cultured in MGIT broth or on Middlebrook agar biplates and isolated colony growth was then identified using MALDI-TOF MS or 16S rDNA gene sequencing. Antimicrobial susceptibility testing was performed using the TREK Sensititre Rapid Growing Mycobacteria Plate. Results: We reviewed total of 1, 840 samples positive for Nocardia spp. Most commonly isolated species included N. cyriacigeorgica (16.9%), N. nova complex (15.7%), N. farcinica complex (14.8%), N. brasiliensis (11.5%) and N. abscessus complex (8.2%). Susceptibilities of the more common Nocardia species are shown in the graph. Source of the positive cultures was variable with majority (>60%) from pulmonary source (sputum, BAL and lung tissue), blood in 5.7% and brain in 3.6%. Most common Nocardia species isolated from brain specimens were N. farcinica complex (24/59) followed by N. abscessus complex (17/59). Most common Nocardia species isolated from blood were N. farcinica complex (38/99) followed by N. nova complex (22/99) and N. cyriacigeorgica (15/99). Conclusion: The antimicrobials that continue to show high activity against most Nocardia species (>95%) are: amikacin, linezolid and TMP/SMX. N. pseudobrasiliensis was noted to have high rates of resistance to TMP/SMX (87%). N. farcinia, N. brasiliensis and N. transvalensis/wallacei complex were >90% susceptible to amoxicillin/clavulanate. Clarithromycin had >99% activity against N. nova complex while both ceftriaxone and doxycycline had> 90% activity against N. abscessus complex. It is crucial to identify Nocardia species and obtain susceptibilities to help better choose the regimen with the best clinical outcome. Disclosures: All authors: No reported disclosures.